2009
DOI: 10.1097/iop.0b013e3181ab5cb1
|View full text |Cite
|
Sign up to set email alerts
|

Limited Nasal Septoplasty by Ophthalmologists During Endonasal Dacryocystorhinostomy: Is It Safe?

Abstract: In the hands of trained ophthalmic lacrimal surgeons, limited nasal septoplasty is an effective and safe procedure during endonasal DCR, allowing better exposure of the surgical field in patients with significant DNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…2,4,6,[8][9][10] Few studies specifically reported the need and frequency of concomitant nasal procedures. [11][12][13] The frequency varied in different studies and ranged from 10-46% for septoplasty, 12.5% for sinus surgeries, up to 4% for middle turbinectomy and isolated polypectomy in 0.34% of the patients. 2,6,[8][9][10][11][12][13][14][15][16] The goals of adjunctive endonasal procedures are to gain an uncompromised free access to lacrimal region thereby making the surgery technically easier as well as preventing apposing mucosal injuries and reducing the chance of post-operative synechiae and by correcting nasal pathologies simultaneously avoiding an unnecessary second surgery.…”
Section: Introductionmentioning
confidence: 98%
“…2,4,6,[8][9][10] Few studies specifically reported the need and frequency of concomitant nasal procedures. [11][12][13] The frequency varied in different studies and ranged from 10-46% for septoplasty, 12.5% for sinus surgeries, up to 4% for middle turbinectomy and isolated polypectomy in 0.34% of the patients. 2,6,[8][9][10][11][12][13][14][15][16] The goals of adjunctive endonasal procedures are to gain an uncompromised free access to lacrimal region thereby making the surgery technically easier as well as preventing apposing mucosal injuries and reducing the chance of post-operative synechiae and by correcting nasal pathologies simultaneously avoiding an unnecessary second surgery.…”
Section: Introductionmentioning
confidence: 98%
“…Zeldovich et al reported a high success rate of 89 % in their cohort of revision DCR, in which 1 mg of betamethasone was injected into the lacrimal sac and scar tissue surrounding the ostium during the surgery [13]. Our group had described the insertion of TA soaked gelfoam in our previous cohort of EE-DCR combined in limited nasal septoplasty with a success rate of 96.4 % [14].…”
Section: Discussionmentioning
confidence: 94%
“…Corticosteroid is known to suppress inflammation and fibroblast recruitment, and supposedly reduce scar formation [13]. It was reported that intraoperative administration of corticosteroid resulted in a high success rate [13][14][15]. We propose that the combined use of MMC, which suppresses the proliferative phase of wound healing, and corticosteroid, which suppresses the inflammatory phase, may have synergistic effect in reducing scar formation, thus contracture or blockage of the osteotomy site in EE-DCR.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…These techniques include Killian or modified Killian mucosal incision, mucosal flap elevation, separation of the septal cartilage and the perpendicular plate of the ethmoid, and excision of deformed portions of cartilage and bone . Even in an article that suggested a limited septoplasty technique, the procedure was not principally dissimilar to traditional ones . Although such techniques must be used to correct overall septal deflections in patients with nasal blockage symptoms, they may be too invasive for patients with high septal deviations alone (thus, with no associated nasal symptoms).…”
Section: Dear Editormentioning
confidence: 99%